Effect of Head and Neck Position on Upper Airway Function in Standardbred Racehorses. (June 2014) - Johnson, K; Noschka, E; Allen, K; Tilbrook, A; Ryan, T; Franklin, S
Abstract : Introduction: Poll flexion may play an important role in the development of dynamic upper respiratory tract (URT) collapse. However, limited investigations have been performed in Standardbred racehorses. Methods: Eight Standardbreds were examined during training, once flexed and once in extension, using a randomised crossover design. Head position was maintained using modified check‐reins and head‐neck angle was recorded. On each occasion horses performed 2 rounds of exercise of 2400 m at ∼35 km/h. Speed and heart rate (HR) were measured and blood obtained before and after exercise. URT endoscopy was performed during the second round. Videos were blinded and URT function assessed. HR, plasma lactate (Lac) and speed were compared for different head positions using paired t‐tests. Cortisol was analysed using repeated‐measures ANOVA and URT function using Fisher's exact tests and paired t‐tests (P<0.05). Results: Data were excluded for one horse where head‐neck angle could not be measured. Flexed and extended head‐neck angles differed significantly (mean: 85.0° vs 97.8°; P = 0.001). All horses showed some form of URT collapse during exercise, although this was only deemed clinically significant in 4 horses with a history of abnormal noise. These horses showed additional abnormalities during flexion. However, mean severity scores did not reach statistical significance (P = 0.08). No significant difference was found for speed, HR or Lac. A significant increase in cortisol was found with exercise (P<0.001). The interaction between time and head position approached significance (P = 0.09) with higher concentrations of cortisol generally occurring in extension rather than flexion. Conclusions: URT abnormalities may be exacerbated with poll flexion. The use of equipment to modify head position may induce a stress response. Ethical Animal Research: This study was approved by the University of Adelaide Animal Ethics Committee and owner informed consent obtained.Sources of funding: University of Adelaide honours projects.Competing interests: none.